2021
DOI: 10.1177/19418744211002676
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors in Elderly Patients With Guillain-Barré Syndrome: Does Age Matter?

Abstract: Introduction: Twenty to 40% of Guillain Barré syndrome (GBS) patients will not be able to walk independently despite effective treatment. Older patients carry additional risks for worse outcomes. Methods: A single center, ambispective cohort study was performed. Only subjects ≥18 years with a 3-month follow-up were included. Elderly patients were considered as a whole if ≥ 60 years. Demographics, CSF and nerve conduction studies were compared. A binomial logistic regression and Kaplan-Meier analyses were carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 27 publications
(35 reference statements)
0
11
0
Order By: Relevance
“…Regarding disease severity, 91.8% of our patients had severe GBS compared to 58.5% reported in ChAdOx1 nCoV‐19 and mRNA‐1273 recipients in the United Kingdom [ 10 ]. This may be attributable to differences in electrophysiological variants, as patients with axonal variants, known to develop a more severe disease course with worse functional outcomes [ 40 , 41 ], accounted for 60.5% of our cases, whereas demyelinating variants accounted for 79.5% of theirs. This may be the result of genetic and environmental differences, as demyelinating variants are more frequent in white populations, while axonal variants are more frequent in Latin American and Asian populations [ 41 ].…”
Section: Discussionmentioning
confidence: 98%
“…Regarding disease severity, 91.8% of our patients had severe GBS compared to 58.5% reported in ChAdOx1 nCoV‐19 and mRNA‐1273 recipients in the United Kingdom [ 10 ]. This may be attributable to differences in electrophysiological variants, as patients with axonal variants, known to develop a more severe disease course with worse functional outcomes [ 40 , 41 ], accounted for 60.5% of our cases, whereas demyelinating variants accounted for 79.5% of theirs. This may be the result of genetic and environmental differences, as demyelinating variants are more frequent in white populations, while axonal variants are more frequent in Latin American and Asian populations [ 41 ].…”
Section: Discussionmentioning
confidence: 98%
“…Risk factors for a poor functional outcome (inability to walk unaided) include older age, severe presentation, and mechanical ventilation requirement 18 . A recent Mexican study reported that patients aged >70 years had a delayed gait recovery compared to younger patients 4 . Mechanical ventilation directly impacts the functional outcome and prognosis.…”
Section: Prognosismentioning
confidence: 98%
“…Small volume PLEX (total exchange of 140 mL/kg over 8 days) is a safe and feasible treatment in low-income countries where IVIg and PLEX are unavailable or unaffordable 10 . In Mexico, the decision between IVIg and PLEX depends on treatment availability, and recent studies report that only 63-75% of patients are so treated 3,4,9 .…”
Section: Therapeutic Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12,37,38 Regarding disease severity, 91•8% of our patients had a severe form (GBS disability score ≥ 3) compared to the 58•5% of severe cases reported by Keh and colleagues among ChAdOx1 nCoV-19 and mRNA-1273 recipients in the United Kingdom. 11 This may be due to differences in electrophysiological variants, as patients with axonal variants, known to develop a more severe disease course with worse functional outcomes, 41,42 accounted for 60•5% of our cases, whereas demyelinating variants accounted for 79•5% of theirs. This can be explained in part by genetic and environmental differences, as demyelinating variants are more frequent in Caucasians, while axonal variants are more frequent in Latin American and Asian populations.…”
Section: Discussionmentioning
confidence: 86%